Penerapan Metode Audio Lingual untuk Meningkatkan Pemahaman Kosakata Bahasa Arab Siswi MA Diniyyah Putri Lampung - Muhammad Zainal Musthofa; Muhammad Ari Wibowo; Masfiyatul Asriyah (Program Studi Pendidikan Bahasa Arab, 2021)
The teaching and learning process is an interaction that is carried out between teachers and learners in a learning process to realize the goals set. The various approaches used in Arabic learning must be translated into learning methods that are different procedures between teachers, students and their environment. From the results of odd semester exam it is known that the student's understanding of Arabic decreases, it is due to the lack of understanding of students in Arabic vocabulary. Therefore, researchers examined the use of AudioLingual methods to improve understanding of Arabic vocabulary of students of class XI K6 MA Diniyyah Putri Lampung, and aimed to know the process of learning Arabic with lingual audio methods. The subject of this study was class XI K6 MA Diniyah Putri Pesawaran Lampung which amounted to 21 students. This research is a qualitative study that takes place in MA Diniyyah Putri Lampung, the data collection methods used are interviews, observations, documentation, oral tests and written tests. While the data analysis used is qualitative descriptive analysis. The results showed that the application of AudioLingual methods to improve students' understanding of Arabic vocabulary can be applied as a support for the success of students in Arabic language learning, it can be proven that there is an increase in each cycle with the acquisition of an average score in cycle I 67.95. Then in cycle II the average student value is 73.14 and at this stage there is an increase with a value of 5.19, then in cycle III with an average student value of 75.93 and the attachment of cycle II is 2.79. Based on the results of research that has been done, it was concluded that this study was successful because of the increase in Arabic learning outcomes in each cycle, this shows that this method is suitable for application in schools